Changes in Working Patterns in a Community Eating Disorder Service; the Impact of the COVID-19 Pandemic and Beyond - Parvathy Mohandas; Maggie McGurgan (BJPsych Open, 2025)
Aims: One of the aims of this project was to look at changes in working patterns within our local Eating Disorder service over time, paying particular attention to changes in rates of accepted referrals, and rates of inpatient admissions during and after the COVID-19 pandemic. A secondary aim was to look at rates of co-morbidity in the local Eating Disorder Population and compare this to the general population of a similar age group. In order to do this, findings for the general population were extrapolated from the Youth Wellbeing Prevalence Study Northern Ireland (YWPS).